DEVELOPMENT OF THE MUSEUM WORK IN DAGESTAN IN THE POST-WAR PERIOD (1945-1965) - Inieva, Z D (History, Archeology and Ethnography of the Caucasus, 2016)
The article analyzes the development of museums in Dagestan over the past two post-war decades. Noting the challenges and accomplishments of Dagestan Central Regional Museum, describes the main exhibitions organized by the museum in the period under review, stock and transport activity.